Surface modification technologies XVIII : proceedings of the eighteenth International Conference on Surface Modification Technologies held in Dijon, France, November 15-17, 2004 /: proceedings of the eighteenth International Conference on Surface Modification Technologies held in Dijon, France, November 15-17, 2004. (2023) - Unknown
No abstract available